Deformation Behavior of Thin Metallic Wires under Tensile and Torsional Loadings - Chen, Ying (KIT Scientific Publishing, 2021)
Size effects are widely observed in the mechanics of materials at the micron scale. However, the underlying deformation mechanisms remain ambiguous, particularly in the presence of strain gradients. In this work, combined microstructural investigations and mechanical tests (tension and torsion) were conducted on polycrystalline gold micro wires to determine the influences of specimen size, grain size, strain rate and loading type on the deformation behavior of the wires.